Higher Education in Saudi Arabia - Saha, Neete (Journal of International Students, 2015)
Institutions in the United States have been popular among Saudi students seeking post-secondary degrees. In fact, Saudi Arabia is one of the highest represented home countries of international students in the US. 44,566 Saudi students enrolled in US colleges and universities for the 2012-2013 academic year, and enrollment numbers for Saudi students have been increasing tremendously over the years (IIE, 2013). Higher education in Saudi Arabia: Achievements, challenges and opportunities (2013), edited by Larry Smith and Abdulrahman Abouammoh, provides insight into this growth. This book suggests that Saudi Arabia wants to improve its higher education system, the goal being to “…achieve ‘world-class’ standards” (p. 5). To accomplish this, Saudi Arabia has invested 160 billion USD into its budget for education.